The Jesus as the second Mosaic Motif?: Intertextual Analysis of the Phrase βασιλεύς in John 12:13 - Sihotang, Orind (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
John 12:13 contains a quotation from Psalm 118:25-26. In the quotation there is an addition of the clause ὁ βασιλεύς τοῦ Ἰσραήλ which is the acclamation of the crowd, thus making a difference in meaning between the text of John 12:13 and the text of Psalm 118:25-26. One of the focuses of this study lies in the phrase βασιλεύς in John 12:13 which is not found in any other Synoptic gospel. The phrase βασιλεύς needs to be explored by looking at the meaning contained in the text of the Septuagint (LXX). The purpose of this study was to reconnect the meaning of βασιλεύς in the text of John 12:13 by relating Psalm 118:25-26 as a quote used by John. The method in this study uses intertextual. Research shows in the Septuagint (LXX) that the phrase βασιλεύς means messenger/leader of Israel. The phrase βασιλεύς also shows that Jesus was the second Moses to lead God's people in deliverance from the bondage of sin to eternal life.